Exploring Variation in Certified Nursing Assistant Assignments From the Perspective of Nursing Home Residents: A Comparison of Adopters and Nonadopters of Consistent Assignment. (November 2019) - Roberts, Tonya J.; Nolet, Kimberly; Bowers, Barbara
Objective: To describe and compare certified nursing assistant (CNA) staffing between adopter and nonadopters of consistent assignment.Data sources: One month of preexisting CNA assignment and scheduling sheets from a purposive sample of 30 homes.Study design: A descriptive comparative study was conducted to calculate and compare numbers of CNAs assigned per resident across homes.Data extraction: Resident names and CNA assignments were abstracted from assignment records and entered into the Advancing Excellence consistent assignment tool to calculate numbers of CNAs assigned per resident.Principal findings: Both variation and overlap existed in the number of CNAs per resident within and between homes. Adopters assigned significantly fewer CNAs per resident.Conclusion: Research is needed to determine how assignment variations affect resident perceptions of quality.